A characterization method for hydrogen embrittlement sensitivity parameters of hydrogen energy storage and transportation equipment materials
Through the test method of load-holding and rapid breaking of hydrogen energy storage and transportation equipment materials in a hydrogen environment, the hydrogen embrittlement susceptibility characterization parameters are calculated, which solves the problem of difficulty in evaluating the hydrogen embrittlement susceptibility of materials in the existing technology and realizes the Evaluation of material performance in low stress environments.
Patent Information
- Application Number
- CN202311353682.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-10-19
AI Technical Summary
The prior art is difficult to effectively evaluate the hydrogen embrittlement sensitivity of hydrogen energy storage and transportation equipment materials in hydrogen environments, and the standard slow tensile test method cannot reflect the performance changes of the materials in low-stress environments.
Adopt a new test method, including protecting the materials in the hydrogen environment, and then rapidly disconnecting, recording the stress strain curve, calculating the elongation of the stress Sexual watch symbols.
This method can more accurately reflect the hydrogen -free sensitivity of hydrogen energy storage and transportation equipment under actual service conditions, avoid the defects of the standard slow stretch test method, and provide more practical and reliable material performance assessment.
Smart Images

Figure CN117629741B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hydrogen storage materials, and in particular relates to a method for characterizing hydrogen embrittlement sensitivity parameters of hydrogen energy storage and transportation equipment materials. Background Art
[0002] Hydrogen energy has the advantages of diverse sources, clean and environmentally friendly, storable and renewable. It is one of the most promising energy sources at present and has broad applications in aviation, power generation, construction, road traffic and other fields. The hydrogen energy industry chain includes hydrogen production, storage, transportation, hydrogenation and use, among which hydrogen energy storage and transportation is the key link connecting the upstream and downstream of the industry chain. At present, hydrogen energy storage and transportation mainly include three methods: gaseous storage and transportation, liquid storage and transportation, and solid storage and transportation. Among them, high-pressure gaseous storage and transportation has become the mainstream hydrogen energy storage and transportation method due to its simple equipment structure, fast hydrogen charging and discharging speed, and wide temperature range.
[0003] To achieve safe and economical storage and transportation of hydrogen energy, the safety problem of hydrogen energy storage and transportation equipment must be solved first. Once hydrogen energy storage and transportation equipment fails, accidents such as leakage, combustion and explosion may occur, causing major casualties and property losses. Its safety problem cannot be ignored. Therefore, it is urgent to clarify the failure mode and damage mechanism of hydrogen energy storage and transportation equipment, and clarify the performance degradation law of materials in hydrogen environment. Hydrogen embrittlement is one of the potential failure modes of hydrogen energy storage and transportation equipment. In order to evaluate the hydrogen embrittlement sensitivity of materials in hydrogen environment, the standard slow tensile test method is generally used. However, for hydrogen energy storage and transportation equipment, this test method has obvious disadvantages: during the slow tensile test in the hydrogen medium environment, when the sample approaches or reaches the yield strain value of the material, the material has a long contact with hydrogen, and at this time, the surface of the material has undergone obvious plastic deformation and generated a large number of dislocations; at the same time, dislocations act as hydrogen traps to promote hydrogen to enter the material. But in fact, the stress level of hydrogen energy storage and transportation equipment is usually in the elastic stress range and is far lower than the yield stress value of the material.
[0004] Therefore, the results of the standard slow tensile test cannot explain the hydrogen embrittlement sensitivity of hydrogen energy storage and transportation equipment materials. There is an urgent need to develop a method for determining the hydrogen embrittlement sensitivity characterization parameters suitable for hydrogen energy storage and transportation equipment based on the characteristics of service conditions. Summary of the invention
[0005] In order to overcome the above-mentioned defects in the prior art, the present invention provides a method for characterizing the hydrogen embrittlement sensitivity parameters of hydrogen energy storage and transportation equipment materials according to the characteristics of service conditions.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for characterizing hydrogen embrittlement sensitivity parameters of hydrogen energy storage and transportation equipment materials, the specific steps are as follows:
[0008] S1. Place the sample in a hydrogen environment and adjust the temperature and pressure so that the test temperature and test pressure reach the design temperature T and design pressure P of the sample respectively;
[0009] S2. Load the sample at a constant loading rate v1 until the sample breaks, and record the test time t from zero loading to fracture of the sample s ;
[0010] S3. Take several identical samples, place them in a hydrogen environment, and adjust the temperature and pressure so that the test temperature and test pressure reach the design temperature T and design pressure P of the sample respectively; then load each sample at a constant loading rate v1 under this environment until the stress level σ of the sample material is reached. h , record the sample from zero loading to σ h The test time t i ; Then hold the load for a time of t h ; After the load holding is completed, the slow tensile specimen is quickly broken at a loading rate of v2, thereby obtaining the stress-strain curve of the entire test process;
[0011] S4. Measure the elongation after fracture of each sample after the sample is broken in step S3. H and area reduction ratio A H According to the stress-strain curve obtained in step S2, the area of the region enclosed by the curve, the stress axis, and the strain axis is calculated to obtain the fracture energy W H ; and calculate the average elongation after fracture of several samples δ H,avg , average section shrinkage A H,avg and the average fracture energy W H,avg ;
[0012] S5, using the average elongation after fracture δ obtained from the above samples H,avg ,δ N,avg , average section shrinkage A H,avg , A N,avg and the average fracture energy W H,avg , W N,avg , calculate the three hydrogen embrittlement sensitivity characterization parameters of the sample in a hydrogen environment I HE,δ ,I HE,A and I HE,W ;
[0013] S6: Three hydrogen embrittlement sensitivity characterization parameters I calculated in step S5 HE,δ ,I HE,A and I HE,W According to the conservative principle, I HE,δ ,I HE,A and I HE,WThe maximum value of is used as a characterization parameter for evaluating the hydrogen embrittlement sensitivity of materials for hydrogen energy storage and transportation equipment.
[0014] Preferably, in step S5, the three hydrogen embrittlement sensitivity characterization parameters I HE,δ ,I HE,A and I HE,W The formulas are as follows:
[0015]
[0016]
[0017] Preferably, in step S6, the formula for taking the maximum value of the hydrogen embrittlement sensitivity characterization parameter is as follows:
[0018] I HE =max{I HE,δ ,I HE,A ,I HE,W}.
[0019] Preferably, in step S3, the hydrogen environment can be replaced by a nitrogen environment or an argon environment, and before the sample is placed in the environmental box, the environmental box is first purged with nitrogen or argon.
[0020] Specifically: Take several identical samples, place them in a nitrogen environment or an argon environment, and adjust the temperature and pressure so that the test temperature and test pressure reach the design temperature T and design pressure P of the sample respectively; then load each sample at a constant loading rate v1 in this environment until the stress level σ of the sample material is h , record the sample from zero loading to σ h The test time t i ; Then hold the load for a time of t h ; After the load holding is completed, the slow tensile specimen is quickly broken at a loading rate of v2, thereby obtaining the stress-strain curve of the entire test process;
[0021] Measure the elongation after fracture of each sample after fracture. H and area reduction ratio A H According to the stress-strain curve obtained in step S2, the area of the region enclosed by the curve, the stress axis, and the strain axis is calculated to obtain the fracture energy W H ; and calculate the average elongation after fracture of several samples δ H,avg , average section shrinkage A H,avg and the average fracture energy W H,avg ;
[0022] The average elongation after fracture δ obtained from the above samples H,avg , δ N,avg , average section shrinkage A H,avg, A N,avg and the average fracture energy W H,avg , W N,avg , calculate the three hydrogen embrittlement sensitivity characterization parameters of the sample in a hydrogen environment I HE,δ ,I HE,A and I HE,W ; Then according to the conservative principle, take I HE,δ ,I HE,A and I HE,W The maximum value of is used as a characterization parameter for evaluating the hydrogen embrittlement sensitivity of materials for hydrogen energy storage and transportation equipment.
[0023] Preferably, in step S1, the design temperature T and design pressure P of the sample are first determined, and then the sample is installed on a slow tensile testing machine with an environmental chamber, and the test environment is adjusted to the values of the design temperature T and design pressure P after hydrogen is filled.
[0024] Preferably, in step S2, the value of the loading rate v1 is 0<v1<2×10 -5 s -1 .
[0025] Preferably, in step S3, the holding time is t h Equal to t s -t i .
[0026] Preferably, in step S3, the value of the loading rate v2 is 0.001s -1 .
[0027] Preferably, the number of samples in step S3 is three or more.
[0028] Preferably, in step S3, before the sample is placed in the environmental box, the environmental box is first purged with nitrogen and then with hydrogen.
[0029] The advantages of the present invention are:
[0030] (1) According to the service characteristics of hydrogen energy storage and transportation equipment in a hydrogen environment, the present invention first holds the material in a hydrogen environment for a certain period of time, and the holding stress level is equivalent to the actual service stress level of the material. The ambient temperature and hydrogen pressure during holding are the same as the actual service temperature and hydrogen pressure of the material, and the holding time is the same as the standard slow stretching to fracture time. Thus, the elongation after fracture, the cross-sectional shrinkage and the fracture energy are obtained, and compared with the test results in a nitrogen environment or an argon environment, so as to obtain the hydrogen embrittlement sensitivity characterization parameters of the hydrogen energy storage and transportation equipment material.
[0031] (2) During the standard slow tensile test, the specimen is above the yield strength load for most of the time (for example, for a material with an elongation of 0.02, this time accounts for 99%). The hydrogen embrittlement sensitivity characterization parameters of the material obtained thereby reflect the effect of hydrogen on the mechanical properties of the material when the material is above the yield point, but cannot reflect the effect of hydrogen on the mechanical properties of the material when the material is below the yield point. However, the test method adopted in the present invention has a total test time that is consistent with the standard slow tensile test time, and the specimen is below the yield strength load for most of the time (for example, for a material with an elongation of 0.02, this time accounts for >99%). The hydrogen embrittlement sensitivity characterization parameters of the material obtained thereby can better reflect the effect of hydrogen on the mechanical properties of the material when the material is below the yield point. The materials of actual high-pressure hydrogen storage and transportation equipment are in service below their yield strength for a long time. Therefore, the hydrogen embrittlement sensitivity characterization parameters obtained by the test method adopted in the present invention can better reflect the hydrogen embrittlement sensitivity of the materials of high-pressure hydrogen storage and transportation equipment under actual use conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic diagram of the process of the present invention.
[0033] Figure 2 These are the stress-strain curves in nitrogen and hydrogen environments. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0035] like Figure 1-2 As shown, a method for characterizing hydrogen embrittlement sensitivity parameters of hydrogen energy storage and transportation equipment materials includes the following steps:
[0036] a. Prepare three standard slow tensile specimens, numbered #7-#9, made of 30CrMoIV material, and use a vernier caliper to measure the specimen diameter and gauge length;
[0037] b. Install the #7 specimen on a slow tensile testing machine with an environmental chamber, purge the environmental chamber with 99.999% pure nitrogen for 3 times, and then purge the environmental chamber with 99.999% pure hydrogen for 3 times, then control the temperature of the environmental chamber at 25°C, the design pressure at 1MPa, and the pressure at 6.6×10 -7 s -1 The strain rate is used to break the specimen, record the load and displacement signals, and record the time required for the specimen to be stretched to fracture;
[0038] c. Repeat step b for samples #8 and #9 to obtain the average stress-strain curves of samples #7-#9, as shown in the attached figure. Figure 2 The C curve in the calculation of yield strength, tensile strength, elongation at break, reduction of area, energy at break and average time from stretching to break, i.e., 48h, i.e., the test results of samples #7-#9 are comparative examples of the invention;
[0039] d. Prepare 6 samples of the same size as in step a, numbered #1-#6, as samples of the embodiments of the present invention, and use a vernier caliper to measure the diameter and gauge length of the samples;
[0040] e. Install the #1 sample on a slow tensile testing machine with an environmental chamber, purge the environmental chamber with 99.999% pure nitrogen for 3 times, and then purge the environmental chamber with 99.999% pure hydrogen for 3 times, and then control the temperature of the environmental chamber at 25°C and 6.6×10 -7 s -1 The strain rate was stretched to the actual service stress level of the sample in this environment, 305.5MPa, the design pressure was controlled to 1MPa, and then the load was maintained for 48h, and finally at 0.001s -1 The sample is quickly broken at a certain rate, the stress-strain curve during the experiment is recorded, and the yield strength, tensile strength, elongation at break, cross-sectional shrinkage, and fracture energy are calculated;
[0041] f. Repeat step e for samples #2 and #3 to obtain the average stress-strain curves of samples #1-#3, as shown in the attached figure. Figure 2 The B curve in the calculation of yield strength, tensile strength, elongation at break, area reduction, and average value of fracture energy;
[0042] g. Install the #4 specimen on a slow tensile testing machine with an environmental chamber, purge the environmental chamber with 99.999% pure nitrogen for 3 times, and then control the temperature of the environmental chamber at 25°C and 6.6×10 -7 s -1 The strain rate was stretched to 305.5MPa, the design pressure was controlled to 1MPa, and then the load was maintained for 48h, and finally at 0.001s -1 The sample is quickly broken at a certain rate, the stress-strain curve during the experiment is recorded, and the yield strength, tensile strength, elongation at break, cross-sectional shrinkage, and fracture energy are calculated;
[0043] h. Repeat step g for samples #5 and #6 to obtain the average stress-strain curves of samples #4-#6, as shown in the attached figure. Figure 2 Curve A in the calculation of yield strength, tensile strength, elongation at break, area reduction, and average value of fracture energy;
[0044] i. Calculation of hydrogen embrittlement sensitivity characterization parameters
[0045]
[0046] According to the above experimental results and the attached Figure 2 It can be obtained that in the above method, the average δ of samples #4-6 is N,avg The average δ of samples #1-3 is 0.145. H,avg The average A of samples #4-6 is 0.141. N,avg The average A of samples #1-3 is 0.57. H,avg The average W of samples #4-6 is 0.52. N,avg 94.35×10 6 J / m 3 , the average W of samples #1-3 H,avg 92.04×10 6 J / m 3 Therefore, the corresponding I can be obtained HE,δ ,I HE,A and I HE,W are 0.028, 0.088 and 0.024 respectively. Therefore, the hydrogen embrittlement sensitivity characterization parameter obtained by the method of the present invention is 0.088, while the hydrogen embrittlement sensitivity characterization parameter obtained by the standard slow stretching method is 0.251. It can be seen that the hydrogen embrittlement sensitivity characterization parameters obtained by the method of the present invention and the standard slow stretching method are quite different, and the attached Figure 2 It can also be explained that there are obvious differences between the results under standard slow stretching and the results obtained by the present invention, that is, standard slow stretching may overestimate the hydrogen embrittlement sensitivity of the material, while the determination method of the present invention can better reflect the hydrogen embrittlement sensitivity of the material of high-pressure hydrogen storage and transportation equipment under actual use conditions.
[0047] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for characterizing hydrogen embrittlement sensitivity parameters of hydrogen energy storage and transportation equipment materials, characterized in that: The specific steps are as follows: S1. Place the sample in a hydrogen environment and adjust the temperature and pressure so that the test temperature and test pressure reach the design temperature T and design pressure P of the sample respectively; S2. Load the sample at a constant loading rate v1 until the sample breaks, and record the test time t from zero loading to fracture of the sample s ; S3. Take several identical samples, place them in a hydrogen environment, and adjust the temperature and pressure so that the test temperature and test pressure reach the design temperature T and design pressure P of the sample respectively; then load each sample at a constant loading rate v1 under this environment until the stress level σ of the sample material is reached. h , record the sample from zero loading to σ h The test time t i ; Then hold the load for a time of t h ; After the load holding is completed, the slow tensile specimen is quickly broken at a loading rate of v2, thereby obtaining the stress-strain curve of the entire test process; S4. Measure the elongation after fracture of each sample after the sample is broken in step S3. H and area reduction ratio A H According to the stress-strain curve obtained in step S3, the area of the region enclosed by the curve, the stress axis, and the strain axis is calculated to obtain the fracture energy W H ; and calculate the average elongation after fracture of several samples δ H,avg , average section shrinkage A H,avg and the average fracture energy W H,avg In step S3, the hydrogen environment can be replaced by a nitrogen environment, and before the sample is placed in the environmental box, the environmental box is purged with nitrogen to obtain δ N,avg , A N,avg , W N,avg ; S5, using the average elongation after fracture δ obtained from the above samples H,avg , δ N,avg , average section shrinkage A H,avg , A N,avg and the average fracture energy W H,avg , W N,avg , calculate the three hydrogen embrittlement sensitivity characterization parameters of the sample in a hydrogen environment I HE,δ ,I HE,A and I HE,W ; S6, three hydrogen embrittlement sensitivity characterization parameters I calculated in step S5 HE,δ ,I HE,A and I HE,W According to the conservative principle, I HE,δ ,I HE,A and I HE,W The maximum value of is used as a characterization parameter for evaluating the hydrogen embrittlement sensitivity of materials for hydrogen energy storage and transportation equipment; In step S3, the holding time t h Equal to t s -t i ; Stress level σ h It is within the elastic stress range and lower than the yield stress value of the material; In step S2, the value of the loading rate v1 is 0<v1<2×10 -5 s -1 ; In step S3, the value of the loading rate v2 is 0.001s -1 ; In step S5, three hydrogen embrittlement sensitivity characterization parameters I HE,δ ,I HE,A and I HE,W The formulas are as follows:
2. A method for characterizing hydrogen embrittlement sensitivity parameters of hydrogen energy storage and transportation equipment materials according to claim 1, characterized in that: In step S6, the formula for taking the maximum value of the hydrogen embrittlement sensitivity characterization parameter is as follows: I HE =max{I HE,δ ,I HE,A ,I HE,W }。 3. A method for characterizing hydrogen embrittlement sensitivity parameters of hydrogen energy storage and transportation equipment materials according to claim 1, characterized in that: In step S1, the design temperature T and design pressure P of the sample are first determined, and then the sample is installed on a slow tensile testing machine with an environmental chamber, and the test environment is adjusted to the values of the design temperature T and design pressure P after hydrogen is filled.
4. A method for characterizing hydrogen embrittlement sensitivity parameters of hydrogen energy storage and transportation equipment materials according to claim 1, characterized in that: The number of samples in step S3 is three or more.
5. A method for characterizing hydrogen embrittlement sensitivity parameters of hydrogen energy storage and transportation equipment materials according to claim 3, characterized in that: In step S3, before the sample is placed in the environmental box, the environmental box is first purged with nitrogen and then with hydrogen.
Citation Information
Patent Citations
Method for evaluating hydrogen cracking resistivity of steel products
JP2010054494A